Perancangan dan Pembangunan Sistem Distribusi Air Bersih - Deni Mulyadi, Cecep; Ubay Caraka, Muhammad (P3M Politeknik Negeri Cilacap, 2021)
Water is one of the natural resources that is very useful for every living thing. Water demand of human will increase in accordance with technological developments that occur in the community, with an effective and efficient regulatory and processing system using plumbing systems. The clean water distribution system in an academic building can work if it is supported by a system of clean water storage that is in accordance with the needs and supported by a pump installation system and piping installation. In the selection of water storage capacity, the selection of pumps and piping systems must be adjusted to the needs of the academic building, it is important to understand the capacity, pipe diameter and installation head. From the calculation results obtained a flow capacity of 1.56 m³/minute with a water tank capacity of 84 m³/day in 8 hours of operational time in one day. A roof water tank capacity of 15 m³ that is able to serve the peak needs of clean water for 30 minutes. While the total head of the installation is 30 meters, so that the selected type of centrifugal pump with a rotation of 3000 rpm, frequency 50 Hz, motor power 15 KW.